PENGARUH PROMOSI, ATMOSFER TOKO, DAN MOTIVASI BELANJA HEDONIS TERHADAP PEMBELIAN IMPULSIF KONSUMEN RITEL MODERN DI KOTA BATAM - Andi Erna Mulyana; Atika Petiwi N.I (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
This study aims to determine the impact of promotion, store atmosphere and hedonic shopping motivation on impulse buying on customers of a famous Department Store in Batam. The data was obtained from distributing questionnaires to 100 respondents whose are customers on that Department Store and made a purchase at least 3 times. The data obtained were analysed by using quantitative analysis with T and F test. The result of the data analysis show that promotion, shopping motivation, and impulse buying has a positive and significant on impulse buying.